Modeling Flows and Concentrations of Nine Engineered Nanomaterials in the Danish Environment - Gottschalk, Fadri (Int J Environ Res Public Health, 2015)
Predictions of environmental concentrations of engineered nanomaterials (ENM) are needed for their environmental risk assessment. Because analytical data on ENM-concentrations in the environment are not yet available, exposure modeling represents the only source of information on ENM exposure in the environment. This work provides material flow data and environmental concentrations of nine ENM in Denmark. It represents the first study that distinguishes between photostable TiO(2) (as used in sunscreens) and photocatalytic TiO(2) (as used in self-cleaning surfaces). It also provides first exposure estimates for quantum dots, carbon black and CuCO(3). Other ENM that are covered are ZnO, Ag, CNT and CeO(2). The modeling is based for all ENM on probability distributions of production, use, environmental release and transfer between compartments, always considering the complete life-cycle of products containing the ENM. The magnitude of flows and concentrations of the various ENM depends on the one hand on the production volume but also on the type of products they are used in and the life-cycles of these products and their potential for release. The results reveal that in aquatic systems the highest concentrations are expected for carbon black and photostable TiO(2), followed by CuCO(3) (under the assumption that the use as wood preservative becomes important). In sludge-treated soil highest concentrations are expected for CeO(2) and TiO(2). Transformation during water treatments results in extremely low concentrations of ZnO and Ag in the environment. The results of this study provide valuable environmental exposure information for future risk assessments of these ENM.